64Abnormal electrogram populations are revealed by atrial programmed stimulation in paroxysmal atrial fibrillation. (October 2014) - Williams, S.; Linton, N.; Harrison, J.; Chubb, H.; Cooklin, M.; Rinaldi, A.; Gill, J.; Wright, M.; O'Neill, M.
Abstract : Introduction: Atrial structural remodelling contributes to the progression of AF and complex fractionated atrial electrograms (CFAE) may represent sites of structural remodelling. However, CFAE is a dynamic and rate-related phenomenon. We sought to compare rate-dependence of CFAE under paced conditions in PAF patients and a control group undergoing LA instrumentation. Methods: Following transeptal puncture rate-dependent fractionation maps were created by pacing from S2=350ms to S2=200ms or ERP from the coronary sinus and high right atrium. Bipolar electrograms were recorded throughout the LA using the PentaRay mapping catheter. Electrograms were filtered from 100-500Hz and peaks were detected with an automated algorithm. Local activation time, electrogram duration and amplitude were measured for each paced electrogram. Results: All electrograms were manually inspected and electrograms were rejected from analysis if the drive train had not captured, the atrial signal displayed a far-field morphology or there was significant artefact on the trace. After rejection of unsuitable electrograms 19, 550 individual atrial bipolar electrograms were analysed from 2000 recording sites. Local activation time increased with pacing rate in the control and PAF groups (Fig. A). In the PAF group, the rate-dependence indicated a dual population with some electrograms delaying normally and others much more significantly (Fig. A, top right). Electrogram duration was not rate-dependent in either group. There was a trend towards reduced electrogram amplitude with increasing pacing rate in both groups that was especially prominent on the septum (Fig. B). Conclusion: Programmed stimulation can identify a distinct population of atrial electrograms in PAF patients that may indicate an underlying atrial substrate. Characterisation of these electrogram populations may reveal further insights into the mechanisms perpetuating atrial fibrillation.